ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA APARATUR DI KANTOR KECAMATAN MARISO KOTA MAKASSAR - Ardiansyah Halim (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study aims to analyze the influence of education, training, job placement, and work climate on the performance of the apparatus at the District Office Mariso Makassar and to analyze the most dominant variables affect the performance of the apparatus at the District Office Mariso Makassar. The research was conducted in September to October 2014, with research sites in the District Office Mariso Makassar, the number of respondents was 73. The data used are primary data and secondary data through interviews and direct observation in the field by using a list of questions (questionnaire). Data were analyzed using multiple regression techniques (multiple regression analysis). The results showed that simultaneous or partially all the independent variables show positive and significant impact on the performance of the apparatus. Factors training is the most dominant factor of influence.